Community knowledge co-creation through participatory video. Issue 3 (September 2015) - Tremblay, Crystal; Jayme, Bruno de Oliveira
This article describes the process and outcomes of a participatory video project with 22 catadore/as (' recyclers ') from recycling cooperatives in the metropolitan region of São Paulo, Brazil. During a week-long workshop (April 2008), leaders from participating cooperatives were trained in video technology, storyboard development, and postproduction media as a strategy to improve community–networking opportunities and to stimulate awareness and education of inclusive and integrated recycling programs. Through a participatory action research initiative, four short documentaries were then co-produced between 2009 and 2011 and a collaborative research design was developed to use the videos as a communication tool for enhancing dialogue with policy makers in three municipalities. This article explores the methodological and theoretical contributions of using participatory video as a strategy for mobilizing community knowledge. This research demonstrates the use of participatory video as a creative avenue to capture and nurture valuable knowledge often on the periphery, which can have powerful impacts when brought into centre stage. It also reviews theories of Community-based Participatory Action Research and Knowledge Democracy as central to expanding processes for participatory development and citizenship. The results reveal enhanced mobilization of this community and document the strengthening of partnerships between recycling cooperatives and municipal governments in the metropolitan region of São Paulo.